Inhibition of Oxygen Evolution in Chloroplasts by Ferricyanide - Drechsler, Zivia (1982)
Preincubation of chloroplasts from pea leaves (Pisum sativum L. cv. Kelvedon) with 0.5 millimolar ferricyanide in the dark, caused a parallel inhibition of the rate of rise of the variable fluorescence and the rate of electron transport. Both reactions were inhibited to a similar extent by varying the time of preincubation, the concentration of ferricyanide during preincubation, and by raising the concentration of salts in the preincubation medium. Ferricyanide treatment of Tris-washed chloroplasts did not inhibit electron transport from the Photosystem II (PSII) electron donor 1,5-diphenylcarbazide to methylviologen. The inhibition of the variable fluorescence rise and of NADP reduction (caused by ferricyanide pretreatment) was bypassed by addition of the PSII electron donor couple hydroquinone/ascorbate. It was concluded that preincubation of chloroplasts with ferricyanide in the dark inhibited electron transport between water and PSII.